Formulation and Evaluation of Amoxicillin Trihydrate Lozenges - Vidyadhara, S; Sasidhar, RLC; Deepti, B; Wilwin, E; Sowjanyalakshmi, B (Dhaka University Journal of Pharmaceutical Sciences, 2015)
In the present investigation an attempt has been made to formulate medicated lozenges containing amoxicillin trihydrate. There are several amoxicillin trihydrate dosage forms in the market such as tablet, capsule, suspension and syrup. Still there is a need for more variant dosage forms which acts effectively and locally. The benefits of the present research work is to increase the retention of the dosage form in oral cavity for increased bioavailability, reduction in gastric irritation and bypassing first pass metabolism. The lozenges were prepared by heating and congealing method employing polyethylene glycol 1500 as matrix base, saccharin sodium (artificial sweetener), stevia (natural sweetener), xanthan gum (polymer), sodium carboxymethyl cellulose (polymer) as other exciepients. The prepared medicated lozenges were characterized for drug content uniformity, hardness, thickness, weight variation, friability and dissolution by standard pharmacopeal methods. The results of the evaluation tests obtained were within the limits. Accelerated stability studies were conducted as per ICH guidelines and found that there wasnt any substantial interaction among the drug, flavour and colour and the prepared formulations were found to be stable. Formulations were tested for drug exciepients interactions subjecting to IR spectral and DSC analyses. The results revealed that there was no major interactions between the drug and polymers used for the preparation of lozenges. Dhaka Univ. J. Pharm. Sci. 14(1): 61-70, 2015 (June)